# How do you combine #sqrt 3 - 2#?

##### 1 Answer

Nov 8, 2015

#### Answer:

You cannot simplify this expression.

However, if you need to rationalize it out of a denominator, you can multiply by its conjugate

#### Explanation:

You cannot combine

For example, to simplify a rational expression like:

#(5-2sqrt(3))/(sqrt(3)-2)#

by multiplying both the numerator and denominator by the conjugate

#(5-2sqrt(3))/(sqrt(3)-2)=((5-2sqrt(3))(sqrt(3)+2))/((sqrt(3)-2)(sqrt(3)+2))#

#=((10-6)+(5-4)sqrt(3))/(sqrt(3)^2-2^2)#

#=(4+sqrt(3))/(3-4) = (4+sqrt(3))/-1 = -4-sqrt(3)#